Pycnodysostosis with recurrent long bone fractures - Chetia, Naba Pallab; Rajan, Aswin Deepak; Medhi, Himashis (International Journal of Research in Orthopaedics, 2019)
Pycnodysostosis is a rare autosomal recessive sclerosing bone disorder characterized by generalized diffuse osteosclerosis. Patients usually have a large head with separated sutures, open fontanels, aplasia of frontal sinuses, obtuse mandibular gonial angle and acroosteolysis of distal phalanges and multiple long bone fractures. We report this case of a 30-year-old female with repeated multiple long bone fractures and other clinico-radiological pathognomonic features of pycnodysostosis.